Study of quality grading standards on Sedum plumbizincicola seedlings for phytoremediation - DAI Yanjiao; HE Aiguo; HU Zhixin; BAI Lianyang; ZHAO Shuo; NIE Yangyang; CHEN Jin (浙江大学学报. 农业与生命科学版)
This paper studied the effects of different seedling quality traits of Sedum plumbizincicola on the removal rate of cadmium (Cd). By the methods of correlation analysis, principal component analysis and clustering analysis, it was found that seedling quality had a great impact on Cd removal efficiency and remediation cost, and stem diameter, branch number, seedling height and Cd content were the important indexes to determine the quality of seedlings. The shoot Cd uptake of the Ⅰ or Ⅱ grade seedling with stem diameter≥5.0 mm, branch number per plant≥2, seedling height≥6.0 cm and seedling Cd content≤5 mg/kg, was more than 200 g/hm2 after 90 d of planting. The remediation efficiencies of the Ⅰ and Ⅱ grade seedlings were over 3.4 times higher than the Ⅳ grade seedling (stem diameter＜4.0 mm, branch number per plant of 0-1, seedling height＜6.0 cm, seedling Cd content≤5 mg/kg), and using Ⅰ and Ⅱ grade seedlings could effectively save labor cost, and reduce or avoid herbicide application. A case of large-area heavy metal contaminated soil remediation was carried out to test this quality classification standard for S. plumbizincicola seedlings, and it was found that the shoot Cd uptake of the Ⅰ or Ⅱ grade seedling was 222.35 g/hm2 after 120 d of planting, and the remediation effect could reach or even higher than that of 6-8 months in previous experiments. In summary, the high-quality S. plumbizincicola seedlings is an important basis for improving remediation efficiency and reducing remediation cost. This study clarifies the quality traits and remediation efficiencies of different grades of seedlings. This standard for grading S. plumbizincicola seedlings is helpful to promote the standardization and mechanization of remediating heavy metal contaminated soil with this plant.